PROFIL KANKER PAYUDARA DI RSUP DR M DJAMIL PADANG PADA TAHUN 2019 - Melya Susanti; Yustisiana Yustisiana; Salmi Salmi (Nusantara Hasana Journal, 2022)
Breast cancer is the most common cancer in women, and is the second most common cancer in the world. The incidence of breast cancer continues to increase every year in both developed and developing countries. The increase in the incidence of breast cancer is thought to be due to an increase in risk factors for breast cancer patients. The risk factors for breast cancer are very multifactorial, including age, gender, genetic factors, reproductive factors, endocrine factors, and dietary factors. In addition, breast cancer also has various types and types, the therapy given is also adjusted to the patient's condition. Amount breast cancer patients come in an advanced stage when  diagnosed the patient has had metastases. This study aims to see how the profile of breast cancer patients at RSUP M DJAMIL in 2019. This research method is descriptive observationalwith a cross-sectional approach. The results of this study were the age of the most breast cancer patients in the age range of 40-49 years (35.1%), the most BMI of breast cancer patients was normal BMI (58.6%), genetic history 99.1%, no family history with breast cancer, the most common stage of breast cancer is stage 4 (63.96%), Invasie ductal carcinoma is the most common type of breast cancer (67.6%), the most common type of therapy is chemotherapy (94%), distant metastases are the most common Most were in the lungs (37.8%). : there are numerous risk  factors causes  breast cancer, the most common type of breast cancer is ductal invasive, patients come already in an advanced stage.